Инструментальное обеспечение в Украине натурных испытаний объектов энергетики, авиационной и ракетно-космической техники на стойкость к воздействию импульсного тока искусственной молнии - Баранов, М.И.; Буряковский, С.Г.; Рудаков, С.В. (Електротехніка і електромеханіка, 2018)
Изложено современное состояние инструментального обеспечения в Украине натурных испытаний объектов промышленной энергетики, авиационной и ракетно-космической техники на стойкость к прямому (косвенному) воздействию на них импульсного тока искусственной молнии. Показано, что подобные испытания технических объектов
на молниестойкость могут проводиться в полевых условиях на уникальном отечественном высоковольтном сильноточном электрооборудовании в соответствии с требованиями нормативных документов США SAE ARP 5412: 2013,
SAE ARP 5416: 2013 и международного стандарта IEC 62305-1: 2010. Описаны основные технические характеристики разработанных и созданных в Украине для целей натурных испытаний отмеченных выше технических объектов
на молниестойкость двух мощных высоковольтных генераторов тока молнии (ГТМ) типа УИТОМ-1 и ГТМ-10/350,
воспроизводящих на испытываемых объектах импульсы тока искусственной молнии с нормированными амплитудновременными параметрами согласно указанных технических документов. Приведены примеры и указаны результаты
натурных испытаний на описанных ГТМ некоторых устройств технических объектов на стойкость к прямому воздействию на них импульсного тока искусственной молнии. Викладено сучасне положення інструментального забезпечення в Україні натурних випробувань об'єктів промислової
енергетики, авіаційної і ракетно-космічної техніки на стійкість до прямої (непрямої) дії на них імпульсного струму
штучної блискавки. Показано, що подібні випробування технічних об'єктів на блискавкостійкість можуть проводитися в польових умовах на унікальному вітчизняному високовольтному сильнострумному електроустаткуванні відповідно до вимог нормативних документів США SAE ARP 5412: 2013, SAE ARP 5416: 2013 і міжнародного стандарту
IEC 62305-1: 2010. Описані основні технічні характеристики розроблених і створених в Україні для цілей натурних
випробувань відмічених вище технічних об'єктів на блискавкостійкість двох потужних високовольтних генераторів
струму блискавки (ГСБ) типу УИТОМ-1 і ГТМ-10/350, відтворюючих на випробовуваних об'єктах імпульси струму
штучної блискавки з нормованими амплітудно-часовими параметрами згідно вказаних технічних документів. Приведені приклади і вказані результати натурних випробувань на описаних ГСБ деяких пристроїв технічних об'єктів на
стійкість до прямої дії на них імпульсного струму штучної блискавки. Purpose. Presentation and analysis of the modern state of the
tooling in Ukraine of model tests of objects of energy, aviation
and space-rocket engineering on resistibility to the action of
pulsed current of artificial lightning. Methodology. Electrophysics bases of technique of high-voltage and high pulsed currents,
theoretical bases of electrical engineering, engineering of high
electric and magnetic fields. Scientific methods of analysis of
research and technical information. Results. Information regarding the modern consisting of Ukraine of high-voltage highcurrent pulsed engineering intended for the leadthrough of
model tests of aircrafts and power objects on resistibility to the
direct or indirect action on them of pulsed current of artificial
lightning in accordance with the requirements of normative
documents of the USA SAE ARP 5412: 2013, SAE ARP 5416:
2013 and International Standard IEC 62305-1: 2010. Basic
technical descriptions are presented of developed and created in
Ukraine for the aims of model tests of the technical objects
marked higher on resistibility to lightning of two powerful highvoltage generators of current of lightning (GCL) of type of
UITOM-1 and GTM-10/350, playback on the tested objects the
pulses of current of artificial lightning with the rationed peaktemporal parameters in obedience to the indicated normativelytechnical documents. Examples are resulted and the results of
model tests are indicated on described domestic GCL of some
elements and devices of the tested technical objects on resistibility to direct action on them of pulsed current of artificial lightning. It is shown that technical descriptions indicated domestic
powerful GCL conform to the high requirements of operating in
the leading countries of the world of normative documents to on
resistibility to lightning objects of industrial energy, aviation
and space-rocket engineering. Originality. First in the summarizing concentrated kind possibilities are shown developed and
created domestic scientists and specialists of unique highvoltage high-current electrophysics equipment for the aims of
leadthrough of integration model tests on resistibility and fire
safety of aircrafts and power objects at lightning strike. Practical value. Application in practice of model tests of objects of
industrial energy, aviation and space-rocket engineering on
complex resistibility and fire safety to the striking action on
them of pulsed current of artificial lightning, generated in discharge circuits of two described powerful domestic GCL, will be
instrumental in the successful decision of global in the world
problem of protecting from lightning of air and surface technical objects and being in them personnel.